2023
DOI: 10.3389/fmicb.2023.1196239
|View full text |Cite
|
Sign up to set email alerts
|

Fermented foods: a perspective on their role in delivering biotics

Abstract: Fermented foods are often erroneously equated with probiotics. Although they might act as delivery vehicles for probiotics, or other ‘biotic’ substances, including prebiotics, synbiotics, and postbiotics, stringent criteria must be met for a fermented food to be considered a ‘biotic’. Those criteria include documented health benefit, sufficient product characterization (for probiotics to the strain level) and testing. Similar to other functional ingredients, the health benefits must go beyond that of the produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…However, the production and consumption of FFs traditionally consumed only in specific countries are changing with globalisation (Rastogi et al, 2022). For instance, products obtained from fermented legumes (e.g., tempeh) are traditionally consumed in several Asiatic countries and are a consistent part of their cultural heritage, but have attracted greater interest from Western populations quite recently (Vinderola et al, 2023). While some of these FFs have continued to be produced using traditional methods of production, that is, depending on local resources and environmental conditions, most have undergone significant technological advancements in order to meet global demand (Panda & Shetty, 2018).…”
Section: Innovations In Food Fermentation To I Mprove Global He Althmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the production and consumption of FFs traditionally consumed only in specific countries are changing with globalisation (Rastogi et al, 2022). For instance, products obtained from fermented legumes (e.g., tempeh) are traditionally consumed in several Asiatic countries and are a consistent part of their cultural heritage, but have attracted greater interest from Western populations quite recently (Vinderola et al, 2023). While some of these FFs have continued to be produced using traditional methods of production, that is, depending on local resources and environmental conditions, most have undergone significant technological advancements in order to meet global demand (Panda & Shetty, 2018).…”
Section: Innovations In Food Fermentation To I Mprove Global He Althmentioning
confidence: 99%
“…Furthermore, it is essential to underscore that a significant portion of the analysed studies showed in Figure 5, and aiming to characterise the gut microbiome, employed the 16S rRNA sequencing method or even more outdated molecular analysis (i.e., DGGE and qPCR), that do not target the entire genomic content of a sample and do not allow to reach the strain-level characterisation. As a consequence, a more in-depth characterisation of the gut microbiome would be necessary in order to explore FFs-gut microbiome relationships, since a strain-level diversity in the gut exists (De Filippis et al, 2019, 2020Tett et al, 2019) and this may influence the impact of dietary or drug treatments (Vinderola et al, 2023). In addition, most of the available interventions are conducted on yogurt and other dairy products.…”
Section: Fermented Foods and Their Effects On Human He Alth Through T...mentioning
confidence: 99%
See 1 more Smart Citation
“…All from an almost forgotten ancient pastime of fermentation, a process that preserves the food from spoilage and increases nutritional value. The rejuvenated global interest in fermented foods, based on scientific research and clinical evidence, augurs well for these types of initiatives in developing countries [ 4 ] .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to their culinary appeal, fermented foods are increasingly recognized for their potential health benefits and role in promoting gut health [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. The fermentation process enhances the bioavailability of nutrients, increases the diversity of microbial species in the gut microbiota, and produces bioactive compounds with antioxidant and anti-inflammatory properties.…”
mentioning
confidence: 99%